The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2000
DOI: 10.1002/(sici)1098-2752(2000)20:1<15::aid-micr3>3.0.co;2-p
|View full text |Cite
|
Sign up to set email alerts
|

Effect of porosity on small-diameter vascular graft healing

Abstract: Experimental studies have reported that complete healing of small-diameter expanded polytetrafluoroethylene (ePTFE) grafts occurs only if the porosity of the graft is increased, thereby allowing ingrowth of perigraft capillaries yielding endothelial cells. This study investigates the effects of varied graft porosity on the healing characteristics of 2-mm internal diameter (ID) ePTFE grafts interposed in the rabbit common carotid artery. Four groups were evaluated: Group A (n = 8) standard (30-microm pores) ePT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0
1

Year Published

2006
2006
2011
2011

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(24 citation statements)
references
References 19 publications
0
23
0
1
Order By: Relevance
“…Endothelialization has been found limited to the perianastomotic regions of 2-mm ePTFE grafts in the rabbit CCA after study at 3 weeks 142 and at 8 weeks. 141 The wide variation in patency of these studies, however, serves to highlight the difficulties in finding consensus among examples of animal models: 20% at 3 weeks and 100% at 8 weeks, respectively.…”
Section: Small-animal Models For the Assessment Of Novel Vascular Conmentioning
confidence: 99%
See 1 more Smart Citation
“…Endothelialization has been found limited to the perianastomotic regions of 2-mm ePTFE grafts in the rabbit CCA after study at 3 weeks 142 and at 8 weeks. 141 The wide variation in patency of these studies, however, serves to highlight the difficulties in finding consensus among examples of animal models: 20% at 3 weeks and 100% at 8 weeks, respectively.…”
Section: Small-animal Models For the Assessment Of Novel Vascular Conmentioning
confidence: 99%
“…181 Recognition of these separate mechanisms to achieve endothelial graft coverage has led to targeted approaches, including coating ePTFE with antibodies designed to capture circulating endothelial progenitor cells 129 or implantation of ePTFE with increased porosity to allow transmural ingrowth. 141 However, therapeutic modulation of conduit pore size is additionally complicated by a number of factors. The relationship between porosity and graft healing is strongly influenced by material-specific characteristics such as the actual dimensions available for ingrowth and cellular orientation, such that 30-m ePTFE is unable to support transmural endothelialization.…”
Section: New Challenges In the Assessment Of Tissue-engineered Vasculmentioning
confidence: 99%
“…The resulting graft hemorrhage is troublesome, increasing operative time and need for blood transfusion. Many studies have been done to develop vascular grafts that are blood tight during implantation, thus eliminating the need for preclotting of the graft and sufficiently porous to facilitate the tissue in‐growth and biological healing 7. Most commonly used method includes coating or impregnation of porous graft with a biodegradable component.…”
Section: Introductionmentioning
confidence: 99%
“…There are a few reports that do not support the positive role of a permeable graft wall in neointima formation and endothelialization. Contreras et al implanted 2‐cm long and 2‐mm ID ePTFE grafts in the rabbit common carotid artery for 8 weeks and found no effect of permeability on either patency rate or neointima formation 45. Wong et al reported that porous and impervious ePTFE vascular patches of 10 × 15 mm 2 in size implanted in dogs for 30 and 60 days did not reveal any significant difference in terms of neointima formation and the cellular composition of the neointima 46.…”
Section: Discussionmentioning
confidence: 99%